Infrastructures Time to Invest - Raad voor het Regeringsbeleid, Wetenschappelijke (Amsterdam University Press, 2008)
Modern societies cannot exist without roads, dams, drinking water, telephone networks and electricity. The recent decades of privatization and globalization have put infrastructural providers at a distance from the influence of government. A lot of the actors in this field no longer act on a regional or national level alone, but are simultaneously active on multiple levels. The essays in this timely book consider the various intersections of public interest, strategic activity and private equity from economic, legal, administrative and technical perspectives. The contributors outline the challenges which future governments will need to meet nationally and globally, such as climate change, reduction of CO2 emissions and global capital flows, to name but a few. This title is available in the OAPEN Library - http://www.oapen.org.
English
Keywords: Politics & government; Sociology; Politics and government; Sociology; Political Science; Sociology